Nutrient attenuation dynamics in effluent dominated watercourses. (1st September 2019) - Acuña, V.; Casellas, M.; Font, C.; Romero, F.; Sabater, S.
Abstract: In-stream attenuation of dissolved and particulate forms of carbon, nitrogen and phosphorus are a crucial ecosystem service, especially in watercourses downstream of chemical pollution point-sources (i.e. wastewater treatment plants). Most chemical-fate models assume that attenuation is directly proportional to the concentration of available dissolved organic carbon, and inorganic nitrogen and phosphorus compounds in watercourses, but there are multiple evidences of saturation and even inhibition of attenuation at higher concentrations. Our current comprehension of nutrient attenuation kinetics in streams remains a limiting factor for the development and calibration of predictive models of the chemical fate of these compounds in rivers, thus hindering the development and implementation of more effective regulatory strategies. Here, we assessed the in-stream attenuation of dissolved organic carbon, inorganic nitrogen (NH4 +, NO2 −, NO3 − ) and phosphorus (PO4 3- ) compounds at increasing concentrations of these compounds, and analyzed the interaction between attenuation kinetics and biofilm structure and function. Specifically, the net balances of these compounds were assessed in artificial streams exposed to eight treatments following the gradient of WWTP contribution to the river flow (0, 14, 29, 43, 58, 72, 86, and 100% of WWTP effluent water). Results indicate that biological in-stream attenuation by a given biofilm of an effluent dominated watercourse might be saturated if exposed for short periods to high nutrient concentrations such as during combined sewer overflow events, but that communities can adapt if exposed long enough to high concentrations, therefore avoiding or at least minimizing saturation. More attention should be therefore given to the management of effluent-dominated watercourses, as reductions in the temporal variability of the discharged wastewater by WWTP might enhance attenuation and thus reduce water quality issues downstream. Graphical abstract: Image 1 Highlights: Poor knowledge of nutrient uptake kinetics constraints predictive models accuracy. Using experimental streams, we assessed uptake kinetics of dissolved nutrients. Monod kinetics prevail on the short-term, but linear kinetics do so on the long-term. WWTP management should avoid short-term fluctuations to favor river water purification.